Improving Communication of Public Health Bachelor's Degree Programs Through Visual Curriculum Mapping - Nelson-Hurwitz, Denise C.; Tagorda, Michelle; Patil, Uday; Kehl, Lisa (Frontiers in Public Health, 2022)
Undergraduate students balance course requirements for the university, college, school, and major. Each set of requirements, including degree-specific curriculum, is intended to promote synergistic interaction of competence, skills, and knowledge, beyond serving as a collection of individual courses. Understanding of curriculum is important for program recruitment as undergraduate students are more informed when deciding between bachelor's degrees options. Among cohorted programs, this understanding is also helpful in communicating and promoting common intellectual experiences. Comprehension of curriculum is especially important for persistence when students are better able to articulate the connections between course and competencies needed to advance in coursework. To improve universal design for learning within program advising, visual curriculum maps were created as infographics to support student understanding of Bachelor of Arts in Public Health degree requirements and specific capstone course pathways. This map is printed as a small booklet and has been pilot tested among prospective students with positive feedback, then implemented in routine advising sessions. Visual maps of capstone requirements were well-received in concept, however constructive student feedback during pilot testing necessitated further revision. Student feedback also encouraged the application of culturally appropriate visuals and analogies to celebrate student diversity. Visual aids such as these may improve access to information among students through universal design, and also improve recruitment, retention efforts, and student buy-in to degree curricula.